2012
DOI: 10.1007/s13280-012-0349-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Global Warming Potentials of Methane and Nitrous Oxide Gases from Rice Paddies under different irrigation regimes

Abstract: A field experiment was conducted in Bangladesh Agricultural University Farm to investigate the mitigating effects of soil amendments such as calcium carbide, calcium silicate, phosphogypsum, and biochar with urea fertilizer on global warming potentials (GWPs) of methane (CH 4 ) and nitrous oxide (N 2 O) gases during rice cultivation under continuous and intermittent irrigations. Among the amendments phosphogypsum and silicate fertilizer, being potential source of electron acceptors, decreased maximum level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 43 publications
9
53
0
Order By: Relevance
“…Biochar has been reported to increase CH 4 emission even at almost 5-6 times higher C content to N-application in fields (Ali et al, 2013;. In addition, wide variation in soil CH 4 emission has been reported for soils with different chemical and physical properties, and under different water regimes (Ali et al, 2013;Cai et al, 1997).…”
Section: Methane Emission Changes With C Supply and Microbial Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Biochar has been reported to increase CH 4 emission even at almost 5-6 times higher C content to N-application in fields (Ali et al, 2013;. In addition, wide variation in soil CH 4 emission has been reported for soils with different chemical and physical properties, and under different water regimes (Ali et al, 2013;Cai et al, 1997).…”
Section: Methane Emission Changes With C Supply and Microbial Activitymentioning
confidence: 99%
“…Biochar, which is the product of the thermal degradation of organic materials in the absence of air (pyrolysis), is used as a soil amendment . Many studies have reported the beneficial effects of biochar in improving the soil quality and crop productivity (Ali et al, 2013;Saarnio et al, 2013;Inubushi, 2013, 2014a;Wang et al, 2012). The renewed interest in biochar comes primarily from its potential role as a long-term C sink in the soil, due to the recalcitrance of its microbial decomposition and chemical degradation (Schneider et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, surveyed funding activities revealed an intense support of biochar research on chemistry & fertility (22%), plant performance (33%), GHG & climate (22%) and technology (22%), but just 1.1% of mentioned funding sources originated from countries low on the human development index. Only three publications mentioned funding from countries with low human development index (Table 1; Ali et al 2012;Deal et al 2012;Sparrevik et al 2013;UNDP 2010). Each of these three studies was devoted to the area of plant performance and 2 of the 3 assessed also effects on chemistry & fertility, GHG & climate and technology.…”
Section: Influence Of Development On Biochar Researchmentioning
confidence: 99%